Firm Value and Optimal Cash Level: Evidence from Indonesian Publicly Listed Non-Financial Firms in 2008-2017 - Natakusuma, Johan (iBuss Management, 2019)
The earlier literature describes cash holdings as having numerous benefits as well as costs that firms have to consider before accumulating cash for transactional and precautionary motives. Most of the literature is focusing on either the benefits or the costs, but some literature such as Azmat (2014) fused both ends into the concept of Optimal Cash Level, in which firm value at its maximum as firms holding cash at that optimal level reap the most benefit and bear the least cost. Thus, this research is conducted to find evidence of an optimal cash level among Indonesian publicly-listed non-financial firms.This research is conducted using 1860 observations coming from non-financial IDX-listed firms for the period of ten years (2008—2017). The result of the regression analysis shows that Indonesian public firms do not adhere to the theory of Optimal Cash Level. The findings could be explained partly by the tendency of firms to avoid underinvestment that may cause failure to capture investment opportunities in the fast-changing Indonesian market. Keywords:Cash, Firm Value, Indonesia, Tobin’s q